Analysis of Auguste Comte's Ideology: Positivism and Implementation of Islamic Education - Muzaki, Yaskur Agil; Amelia, Dwi Rizqi; Sarianto, Debi; Junaedi, Mahfud; Sabrina, Rifdah; Yelliza, Merri (Suluah Pasaman, 2023)
This study aims to analyze Auguste Comte's thinking about positivisme and how this thinking can be implemented in an Islamic context. This research uses the qualitative method with content analysis approach, all data taken from various sources which are derived from books, theories and expert opinion. All data that has been collected are analyzed thematically, in other words the themes that have been obtained are described comprehensively and deeply. The results of the analysis from this study reveal several important aspects of the biography of Auguste Comte. Auguste Comte was a French philosopher who lived in the 19th century. Auguste Comte's positivist philosophical thinking includes three stages of development of human science: the theological stage, metaphysical stage, and positive stage. Contribution of Auguste Comte's positivist thought to Islam. Even though Comte's thought explicitly rejected religion and metaphysics, there are elements of positivism that can be applied in the Islamic context.